Molecular characterization and antifungal susceptibility of Cryptococcus neoformans strains collected from a single institution in Lima, Peru - Bejar V. (2015)
Mercedes Tello is supported by a scholarship for postgraduate studies in Cellular and Molecular Biology, from the Consejo Nacional de Ciencia y Tecnología (CONCYTEC-Perú). Ericson Gutierrez is supported by a scholarship for postgraduate studies in Demography and Population Health,from the Belgian Development Q6 Cooperation CTB-Perú (L11PER016)